2011
DOI: 10.1186/1758-3284-3-3
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric oncology: comparing health related quality of life in head and neck cancer patients

Abstract: BackgroundPopulation ageing is increasing the number of people annually diagnosed with cancer worldwide, once most types of tumours are age-dependent. High-quality healthcare in geriatric oncology requires a multimodal approach and should take into account stratified patient outcomes based on factors other than chronological age in order to develop interventions able to optimize oncology care.This study aims to evaluate the Health Related Quality of Life in head and neck cancer patients and compare the scores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 35 publications
4
19
0
4
Order By: Relevance
“…This mode of conduct is similar to that which was proposed in a recent study regarding geriatric patients with HNC (10). …”
Section: Discussionsupporting
confidence: 88%
“…This mode of conduct is similar to that which was proposed in a recent study regarding geriatric patients with HNC (10). …”
Section: Discussionsupporting
confidence: 88%
“…Due to the number of patients treated with radiotherapy and the decreasing dosages and smaller fields of irradiation currently used, it is likely that the number of secondary tumors will decrease in the coming decades. The lower percentage in older patients treated with multimodality treatment can be explained by the choice of both physicians and older patients to go for care instead of cure in these often frail patients [3840]. Localization in the maxillary region exceeded mandible localizations, which is not in line with other publications [41].…”
Section: Discussionmentioning
confidence: 92%
“…On studying the various lesion groups, it was noted that malignancies and potentially malignant disorders (PMD) were the most predominant lesions and they envelop a huge margin of geriatric cases (62%) reporting to the institution of which malignant epithelial neoplasms such as oral squamous carcinoma (94%) account for the major group of lesions. Frequent mutations and hypomethylation of the DNA known to occur in ageing population, are predisposing factors for tumour cell transformation and oncogene activation, thereby favouring tumorigenesis. Studies have also shown that old are more likely to develop cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent mutations and hypomethylation of the DNA known to occur in ageing population, are predisposing factors for tumour cell transformation and oncogene activation, thereby favouring tumorigenesis. Studies have also shown that old are more likely to develop cancer. Head and neck oral squamous cell carcinoma is rising rapidly in India, and with the concurrent rise in geriatric population, geriatric oncologies are likely to be the most formidable mortality factor in future.…”
Section: Discussionmentioning
confidence: 99%